Pengembangan media pembelajaran peta digital berbasis thinglink materi sejarah Kerajaan Islam Sumatra di SMAN 2 Malang - Rama Maulana Muhammad Razif; Slamet Sujud Purnawan Jati; Ahmad Khoirul Yaskhudi (Universitas Negeri Malang, 2022)
Innovation and development of quality learning media is one of the demands in the modern era. Thus, teachers must have the skills to adopt the use of technology as a learning medium that helps improve the quality of learning. The purpose of this research is to produce a digital map learning media based on Thinglink on the material of the history of the Islamic kingdom in Sumatra and to test its effectiveness in learning. The subject of this research is class X IPS 1 SMAN 2 Malang with a total of 25 students. The learning media development model used is the ADDIE model which consists of 5 (five) stages, namely analyze, design, develop, implement, evaluate. Learning media created using the thinglink website and the Corel Photo Paint X7 application. The media produced is in the form of a digital map which contains an explanation in the form of PPt links, Youtube videos, and pictures of the territory of the kingdom. It is hoped that the Thinglink media can help students of class X Social Sciences understand more about the history of the Islamic Kingdom in Sumatra. The results of this study obtained results of 88.6 percent (very valid) from material and media experts. And the results obtained are 82.0 percent (very effective) in small group trials, and 84.0 percent (very effective) in large group trials. And it can be concluded that this media is suitable for use in history learning for class X at the high school level/equivalent. Thinglink media is also expected to increase students' motivation and learning outcomes in learning history.Inovasi dan pengembangan media pembelajaran yang berkualitas merupakan salah satu satu tuntutan di era modern. Demikian, guru harus memiliki keterampilan untuk mengadopsi pemanfaatan teknologi sebagai media pembelajaran yang membantu peningkatan kualitas belajar. Tujuan dari penelitian ialah menghasilkan media pembelajaran peta digital berbasis Thinglink pada materi sejarah kerajaan Islam di Sumatra dan menguji keefektifannya dalam pembelajaran Subjek penelitian ini adalah kelas X IPS 1 SMAN 2 Malang dengan jumlah 25 siswa. Model pengembangan media pembelajaran yang digunakan adalah model ADDIE yaitu terdiri dari 5 (lima) tahapan yaitu analyze, design, develop, implement, evaluate. Media pembelajaran yang dibuat menggunakan website thinglink dan aplikasi Corel Photo Paint X7. Media yang dihasilkan berbentuk peta digital yang didalamnya memuat penjelasan berupa link PPt, video Youtube, dan gambar dari wilayah kekuasaan pada kerajaan. Harapannya media Thinglink dapat membantu siswa kelas X IPS lebih memahami materi sejarah Kerajaan Islam di Sumatra. Hasil penelitian ini diperoleh hasil 88.6 persen (sangat valid) dari ahli materi dan media. Dan diperoleh hasil 82.0 persen (sangat efektif) pada uji coba kelompok kecil, dan 84.0 persen (sangat efektif) pada uji coba kelompok besar. Dan dapat ditarik kesimpulan bahwa media ini layak digunakan dalam pembelajaran sejarah kelas X tingkat SMA/sederajat. Media Thinglink juga diharapkan dapat meningkatkan motivasi dan hasil belajar siswa dalam pembelajaran sejarah.